The Influence of Digital Marketing, Online Customer Reviews and Millennial Culture on Purchase Decisions on Gacoan Noodles (Study on Gacoan Noodle Consumers Mojokerto Branch) - Erika Berliana Farchan Putri; Evi Fitrotun Najiah; Mohammad Yaskun (Sean Institute, 2024)
This study aims to determine the influence of Digital Marketing, Online Customer Review and Millennial Culture on purchase decisions on Mie Gacoan (a study on consumers of Mie Gacoan Mojokerto branch) by using questionnaires as research instruments where the sample in this study is consumers of Mie Gacoan Mojokerto branch. The purpose of this study is to find out how Digital Marketing, Online Customer Review and Millennial Culture influence purchase decisions, whether the variables of Digital Marketing, Online Customer Review and Millennial Culture have an influence on purchase decisions partially and simultaneously, and which variables are the most dominant. This research is a quantitative research, this study contains a total of 98 samples taken from consumers of Mie Gacoan Mojokerto branch. The sample extraction technique in this study is based on the notation of the minimum sample large formula by the Lameshow formula. The data analysis methods used were: validity test, reliability test, classical assumption, multiple linear regression analysis, determination coefficient and hypothesis testing of t-test and F-test.